Temporal variability of radon in a remediated tailing of uranium ore processing – the case of Urgeiriça (central Portugal). (April 2015) - Barbosa, S.M.; Lopes, F.; Correia, A.D.; Barbosa, S.; Pereira, A.C.; Neves, L.F.
Abstract: Radon monitoring at different levels of the cover of the Urgeiriça tailings shows that the sealing is effective and performing as desired in terms of containing the strongly radioactive waste resulting from uranium ore processing. However, the analysis of the time series of radon concentration shows a very complex temporal structure, particularly at depth, including very large and fast variations from a few tens of kBq m −3 to more than a million kBq m −3 in less than one day. The diurnal variability is strongly asymmetric, peaking at 18 h/19 h and decreasing very fast around 21 h/22 h. The analysis is performed for summer and for a period with no rain in order to avoid the potential influence of precipitation and related environmental conditions on the radon variability. Analysis of ancillary measurements of temperature, relative humidity, wind speed and wind direction, as well as atmospheric pressure reanalysis data shows that the daily averaged radon concentration in the taillings material is anti-correlated with the atmospheric pressure and that the diurnal amplitude is associated with the magnitude of atmospheric pressure daily oscillations. Highlights: The temporal variability of radon at the Urgeiriça tailing is examined. The cover of the tailing is effective in containing the strongly radioactive waste. Radon concentration varies with depth and exhibits very large sub-daily variations. The daily variability is strongly asymmetric and non-stationary. Apparent influence of atmospheric pressure on radon concentration patterns.